Absolute free energies of binding of peptide analogs to the HIV-1 protease from molecular dynamics simulations - Bartels, Christian; Widmer, Armin; Ehrhardt, Claus (Journal of computational chemistry, 2005)
The constants of binding of five peptide analogs to the active site of the HIV‐1 aspartic‐protease are calculated based on a novel sampling scheme that is efficient and does not introduce any approximations in addition to the energy function used to describe the system. The results agree with experiments. The squared correlation coefficient of the calculated vs. the measured values is 0.79. The sampling scheme consists of a series of molecular dynamics integrations with biases. The biases are selected based on an estimate of the probability density function of the system in a way to explore the conformational space and to reduce the statistical error in the calculated binding constants. The molecular dynamics integrations are done with a vacuum potential using a short cutoff scheme. To estimate the probability density of the simulated system, the results of the molecular dynamics integrations are combined using an extension of the weighted histogram analysis method (C. Bartels, Chem. Phys. Letters 331 (2000) 446–454). The probability density of the solvated ligand–protein system is obtained by applying a correction for the use of the short cutoffs in the simulations and by taking into account solvation with an electrostatic term and a hydrophobic term. The electrostatic part of the solvation is determined by finite difference Poisson–Boltzmann calculations; the hydrophobic part of the solvation is set proportional to the solvent accessible surface area. Setting the hydrophobic surface tension parameter equal to 8 mol−1 K−1 A−2, absolute binding constants are in the μM to nM range. This is in agreement with experiments. The standard errors determined from eight repeated binding constant determinations are a factor of 14 to 411. A single determination of a binding constant is done with 499700 steps of molecular dynamics integration and 4500 finite difference Poisson–Boltzmann calculations. The simulations can be analyzed with respect to conformational changes of the active site of the HIV‐1 protease or the ligands upon binding and provide information that complements experiments and can be used in the drug development process. © 2005 Wiley Periodicals, Inc. J Comput Chem 26: 1294–1305, 2005